De novo abnormalities identified by fluorescence in situ hybridization during follow-up confer poor prognosis in Chinese multiple myeloma - Chen, Shumin; Gao, Lu; Feng, Lin; Wang, Zheng; Li, Ye; Liu, Qing; Song, Wenjie; Kong, Shu; Liu, Yang; Lu, Jin; Chang, Yingjun; Huang, Xiaojun; et al. (Frontiers in Medicine, 2025)
BackgroundAlthough there is evolving consensus to re-evaluate cytogenetic features during follow-up in multiple myeloma (MM), longitudinal studies on cytogenetic evolution in Chinese MM patients are still lacking. Our aim was to highlight the importance of ongoing monitoring of cytogenetic characteristics and shed light on the implications of clonal evolution in Chinese MM patients.Patients and methodsThe clinical data of 230 MM patients were retrospectively analyzed, including 100 patients were continuously monitored for cytogenetic abnormalities by fluorescence in situ hybridization (FISH).Results49 out of 100 patients acquired de novo FISH abnormalities during follow-up, which were associated with disease progression (p = 0.003) and inferior progression free survival (PFS) (median 31 vs. 51 months, p = 0.032). Patients with ≥2 de novo FISH abnormalities had poorer PFS (median 24 vs. 45 months, p = 0.003) when compared to those with l or no de novo FISH abnormality. Patients who acquired new abnormalities within 31 months since diagnosis had significantly worse PFS (median: 20 vs. 41 months, p < 0.001) and Overall Survival (OS) (median: 61 vs. 100 months, p = 0.008) compared to those who acquired new abnormalities after 31 months. When gain/amp 1q21, del(17p), t(4;14), and t(14;16) were classified as high risk abnormalities (HRA), patients with ≥2 HRA had a shorter PFS (median 28 vs. 49 months, p = 0.038) and OS (median 75 vs. 107 months, p = 0.040) when compared to those without HRA.ConclusionRe-evaluation of cytogenetic characteristics by serial FISH tests is important in MM patients. De novo FISH abnormalities during follow-up are adverse prognostic factors, especially when ≥2 new FISH anomalies and acquired new abnormalities within 31 months since diagnosis are presented, and the presence of ≥2 HRA during the disease process are associated with poor survival in Chinese MM patients.